Factors contribute wasiyyah practice among Malaysian muslim : case study of Amanah Raya Johor Bahru - Mohamed Rafi, Nurul Auni Syamimi (2019)
The word Islamic will or called wasiyyah in Arabic is derived from the root word of wassa, which means order, advice, promising, or giving something valuable after death. In Arabic, wasiyyah means to ask someone to do things in her absence, either during his lifetime or after his death Abd, Suraiya, Amalina, & Ghani, (2019).This study is focusing on "Wasiyyah practice among Amana Rakyat Berhad Johor prepared for final project paper in completion of the courses in BBA (Hons) Finance. Islamic estate planning industry in Malaysia has grown and now offers a variety kind of products to facilitate Malaysian Muslims to manage and improve their estate planning matters. Hence, this study aims to look at the practice of making wasiyyah in Malaysia and investigate factors that influence Muslims to do it. The method of analysis employed in this study include Reliability Test, Descriptive Analysis, Correlation Analysis, Regression Analysis and One-Way Analysis of Variance (ANOVA), Pearson and Correlation as well as Multiple Regression. The correlation analysis showed a significant and positive correlation between wealth management, institutional factor and religiosity toward Islamic will practice. These results suggest that the government and Islamic estate planning industry should put a greater emphasis on attracting and educate Muslims to manage and plan their wealth well during their lifetime